The Ideology of the Main Female Character in the Novel Amba by Laksmi Pamuntjak - Erlinda A. Suleman; Herson Kadir; Yunus Dama (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research examines Laksmi Pamuntjak's novel, Amba, which tells the story of the main female character's struggle to find freedom and equality with men. Initially, the main female character views freedom as a means to happiness. However, she experiences destruction and loss that render her unaware of her rights as a woman. This situation drives her to resist patriarchy through a transformation into a woman with freedom of choice, freedom of opinion, responsibility, and independence. This research focuses on two issues: feminine transcendence as viewed from the perspective of women's existence in Laksmi Pamuntjak's novel, Amba. This study is analyzed using Simone de Beauvoir's existentialist feminist theory in her book, The Second Sex, which discusses the transcendence of women's freedom and awareness in determining their identity. The method used is descriptive qualitative, using reading, observing, and note-taking techniques. The research results show that the main female character successfully discovers her identity and truth through her search for a livelihood on Buru Island, leading her to become an independent, critical, and persistent woman. This struggle reflects a woman's efforts to achieve full existence and recognition. The conclusions from the research findings indicate that the main female character successfully fights for women's rights through her efforts to transcend her limitations. The main female character maintains her honor as a mother and the love of a man.